ANALISIS KINERJA BADAN PEMBERDAYAAN MASYARAKAT DAN PEMERINTAHAN DESA KOTA DENPASAR DALAM PENGELOLAAN BANTUAN KELURAHAN - aricahya, agung anak; suyana, made utama; yuliarmi, ni nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
This research was conducted at BPMPD Denpasar. The goal is to determine the performance of Denpasar BPMPD village aid management has been effective and efficient so that what is programmed is reached, which will be measured from the perspective empar the financial perspective, the perspective of service users, internal process perspective and learning and growth perspective either partially as well as a whole by using the Balanced Scorecard approach. Results of the analysis showed BPMPD performance in the management of village assistance in terms of financial perspective shows the performance of the categories with a value of 74.42 percent. Performance from the perspective of service users showed good performance category with a value of 77.08 percent. Performance of the internal process perspective shows excellent performance with 99.50 percent while the value for the learning and growth perspective also shows very good performance with a value of 97.14 percent. BPMPD overall performance in terms of four perspectives with the calculation of the composite index is at a good qualifying performance with value 85.91 percent. In order to improve the performance of the management of village assistance are advised to maximize the planning, implementation and realization of the budget, increasing the dissemination and coordination with the village in order to expedite the disbursement of aid wards.
Keywords: Kinerja BPMPD Kota Denpasar, Balanced Scorecard